Genetic and clonal structures of the tree species Tilia cordata mill. in remnants of ancient forests in Denmark. Issue 3 (10th April 2019) - Erichsen, Eva Ortvald; Wolff, Kirsten; Hansen, Ole K.
Abstract: The insect‐pollinated forest tree Tilia cordata Mill. grows today in small fragmented populations in Denmark and other western European countries but was, in prehistoric times, a dominating species and is considered an indicator species for ancient forest. The species is known to propagate both sexually and vegetatively, forming clonal groups. Few studies have been made on the species' population genetics and on how clonality affects the population structure. The aim of this study is to evaluate the Danish gene pool by estimating genetic diversity and differentiation, as well as through exhaustive sampling describe clonal structures in some of the populations. Genetic analysis was carried out using nine nuclear microsatellite markers in nine populations, of which four were exhaustively or partly exhaustively sampled. The markers showed a high degree of genetic diversity but low differentiation between populations, with no geographic‐related structure. Clonal structures were found in eight out of the nine populations. In the exhaustively sampled populations, recruitment strategies included both sexual and clonal reproduction with indications that clonality may be enhanced by management and other disturbances. Abstract : The tree species Tilia cordata, an indicator species for ancient forest, is known to propagate both sexually and vegetatively. Here we evaluate the genetic diversity and differentiation in the Danish gene pool and characterize the occurance of clonal structures in different populations.